Intertextuality in the socio-cultural elements of Howl’s Moving Castle / Ng Yao Jia - Ng , Yao Jia (2019)
Howl’s Moving Castle, a popular animated feature film produced by Studio Ghibli in 2004, chronicles the transformation and growth of Sophie Hatter after having been cursed by the Witch of the Waste and forced to leave her sheltered life behind. This dissertation will undertake an intertextual analysis to examine how director Hayao Miyazaki has included socio-cultural intertextual references in the feature film. The analysis will be guided by concepts of intertextuality to identify the socio-cultural references which were found in the feature film. The results will indicate the semiotic effects in the use of the intertextual references and how it may affect the interpretation for audience from different background.